Flipped classroom as a tool for the achievement of autonomous learning in university students - Ventosilla Sosa, Danny Nicke (2021)
The research aimed to determine the influence of the flipped classroom as a tool for the achievement of autonomous learning in university students. The type of study that was used was applied and the experimental design of a quasi-experimental sub type. The sample consisted of 73 students distributed in 2 groups of which one was the controlgroup (37) and the other theexperimental group (36), students of both sexes, for which an intentional Non-Probabilistic sampling was used. In relation to the technique, this was the survey as instruments the questionnaire that was applied virtually whichwent through two phases before being applied to the study sample (validity and reliability), in relation to the reliability a value was obtained of 0.864according to KR20.The pre-test results in relation to autonomous learning 38.9% and 43.2% of the students in the control group (CG) andexperimental group (EG) maintain a low level, likewise, 58.3% and 43, 2% present a medium level, for their part, 2.8% of the control group and 13.6% of the experimental group were at the high level. It was concluded thatthe flipped classroom allowsthe student to learn autonomously, incorporating TICas an innovative element in the transformation of the acquisition of new learning in a responsible manner.